Strategi Pemasaran STP (Segmenting, Targeting, Dan Positioning) Pada Produk Kecantikan House Of Beauty Cabang Kota Pematangsiantar - Sri Aderafika Sani; Nuri Aslami (MAMEN: Jurnal Manajemen, 2022)
This study aims to explain the marketing strategy of STP (Segmenting, Targeting and Positioning) in marketing the beauty products of House of Beauty Pematangsiantar. The research was taken based on information from the head of the branch manager, customer service, employees and clients of the House of Beauty Pematangsiantar. Thiis research is a qualitatiive research with descriptive method. From thee research that has been done, the researcheer concludes that the segmenting strategy carried out by the Pematangsiantar House of Beauty is based on geographic and demographic segmentation. The geographic segmentation of the targeted sector is the sector, especially Pematangsiantar City. While the demographic segmentation is students and university students, civil servants, private employees, and mothers in the age range of 17-60 years. For the targeting house of beauty in Pematangsiantar, the main ones are students, women, and private employees. The positioning carried out by the house of beauty is with the concept of Nature Meets Technology which is a combination of active herbal cosmetic ingredients with sophisticated and modern technology beauty equipment. House of Beauty has standardized quality equipment based on medical analysis and consultation, so that it can provide the best results.